Performance of fractional PID algorithms controlling nonlinear systems with saturation and backlash phenomena - Barbosa, Ramiro S. (2007)
The development of fractional-order controllers is currently one of the most promising fields of research. However, most of the work in this area addresses the case of linear systems. This paper reports on the analysis of fractional-order control of nonlinear systems. The performance of discrete fractional-order PID controllers in the presence of several nonlinearities is discussed. Some results are provided that indicate the superior robustness of such algorithms.